2014
DOI: 10.4172/2157-7099.1000259
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H:Quinone Oxidoreductase 1 Expression in Human Primary Melanotic Melanomas of the Skin

Abstract: NAD(P)H:quinone oxidoreductase 1 (NQ01; DT-diaphorase; DTD) is a two-electron reducing enzyme which is often over-expressed in cancers and can activate quinones to form cytotoxic species. This over-expression is used as target in the design of novel anti-cancer drugs. DTD is also expressed in normal tissues, but little is known about its "body mapping". Because of the dearth of information on the cell-specific expression of DTD in pigmentproducing cells of the skin, we analysed its expression in normal and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…DT-Diaphorase also functions as antioxidant enzyme [ 20 ]. Apart from facilitating the two electron reduction of many xenobiotics inducing carcinogenesis [ 38 ], it reduces quinones to prevent the formation of semi quinones and protect from its reactive intermediate metabolites. These findings of the present work suggested that gallic acid and acetylsalicylic acid have a chemopreventive ability and likely to protect against the detrimental effects of toxic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…DT-Diaphorase also functions as antioxidant enzyme [ 20 ]. Apart from facilitating the two electron reduction of many xenobiotics inducing carcinogenesis [ 38 ], it reduces quinones to prevent the formation of semi quinones and protect from its reactive intermediate metabolites. These findings of the present work suggested that gallic acid and acetylsalicylic acid have a chemopreventive ability and likely to protect against the detrimental effects of toxic compounds.…”
Section: Discussionmentioning
confidence: 99%